Distinct esophageal adenocarcinoma molecular subtype has subtype-specific gene expression and mutation patterns - Xiangqian Guo; Yitai Tang; Wan Zhu (BMC Genomics, 2018)
Abstract Background Esophageal carcinoma (EC), consists of two histological types, esophageal squamous carcinoma (ESCC) and esophageal adenocarcinoma (EAC). EAC accounted for 10% of EC for centuries; however, the prevalence of EAC has alarmingly risen 6 times and increased to about 50% of EC in recent 30 years in the western countries, while treatment options for EAC patients are still limited. Stratification of molecular subtypes by gene expression profiling methods had offered opportunities for targeted therapies. However, the molecular subtype in EAC has not been defined. Hence, Identification of EAC molecular subtypes is needed and will provide important insights for future new therapies. Results We performed meta-analysis of gene expression profiling data on three independent EAC cohorts and showed that there are two common molecular subtypes in EAC. Each of the two EAC molecular subtypes has subtype specific expression patterns and mutation signatures. Genes which were over-expressed in subtype I EACs rather than subtype II EAC cases, were enriched in biological processes including epithelial cell differentiation, keratinocyte differentiation, and KEGG pathways including basal cell carcinoma. TP53 and CDKN2A are significantly mutated in both EAC subtypes. 24 genes including SMAD4 were found to be only significantly mutated in subtype I EAC cases, while 30 genes including ARID1A are only significantly mutated in subtype II EACs. Conclusion Two EAC molecular subtypes were defined and validated. This finding may offer new opportunities for targeted therapies.